Pharmacokinetics and bacteriological efficacies of apalcillin and cefpiramide in experimental pneumococcal meningitis. - Sato, K (1984)
Rabbits with experimentally induced pneumococcal meningitis were given single 25-mg/kg doses of apalcillin or cefpiramide. Mean percentages of the drug concentration in cerebrospinal fluid versus that in blood serum were 7.6% with apalcillin and 3.9% with cefpiramide. Bactericidal activity in cerebrospinal fluid resulted in mean reductions of from 4 to 5 log10 CFU/ml, and cerebrospinal fluid cultures became sterile for four of six animals treated with each drug.